Dendracalamus Asper (D. Asper) Pulp and Paper-Making Properties Development by Using Soda Pulping - Wee, Aldrius; Main, Nor Mazlana (Progress in Engineering Application and Technology, 2023)
The study sought to ascertain the potential usefulness of an 18% NaOH charge on D. Asper (Buluh Betong) for pulp and paper production. The pulping procedure employed soda pulping. The pulping conditions involved utilising the same amount of NaOH and heating for 1.5 h and 2 h, respectively. The production of pulp, paper, and its attributes complied with TAPPI and MS ISO guidelines. The foundation weight for the manufacture of the paper sheets was 120 gsm. 43% of the screened yield was produced by pulp from both conditions. Regarding the tear, tensile, and bursting index, there was no lot of variation between the conditions based on ANOVA analysis. Both conditions were in the same class of means. Physical characteristics included the following: paper density for 1.5 h was 0.4533 kg/cm2 and 0.5822 kg/cm2 for 2 h, thickness for 1.5 h was 245.28 m and 200.96 m, and the grammage obtained was 117 gsm for both situations. Investigations into mechanical properties included tensile indexes of 3.43 N.m/g and 4.592 N.m/g, tearing indexes of 3.45 mN.m2/g and 3.18 mN.m2/g, and burst indexes of 3.67 kPa.m2/g and 3.47 kPa.m2/g, respectively, for 1.5 h and 2 h. The virgin soda pulp and paper from D. Asper bamboo had demonstrated promise as a raw material for manufacturing paper. To enhance the quality of the pulp and paper, additional detailed research will be required in the future. D. Asper fibre has a significant potential for usage in the paper-making sector because of its characteristics for soda pulping. The study's findings will also be used to build and improve sustainable paper production while avoiding environmental contaminating factors.